Refrigerated Silver Solution is as Good as Fresh Preparation in the Demonstration Of Reticulin Fibres - Muhammed Abdurrasheed Ola*, Muhammad Ahmad Tangaza, Balogun Musbau Olusesan, Olutunde Oluwumi Abiola (Sokoto Journal of Medical Laboratory Science)
The objective of this study is to investigate the effect of refrigeration on the silver solution prepared for reticulin demonstration. Tissue blocks of Wistar Rat liver were retrieved from the Animal Tissue Block Archive of the Department of Pathology, University of Ilorin Teaching Hospital, Ilorin. Five normal blocks were randomly selected and Five (5) serial sections labeled A to E were made from each block. The group A sections were stained for reticulin fibres using fresh silver bath (Gordon and Sweet method), and the other groups (B-E) were stained with the remaining silver bath refrigerated at 4 ± 2oC. This was done every two weeks for eight weeks. The histological evaluations revealed no morphological difference in the reticular fibres staining using fresh and refrigerated silver bath for up to a period of eight weeks. Contrary to some authors and the general belief that silver bath must be prepared fresh at every point of use for reticulin demonstration. This study has proven that Medical Laboratory Scientists can prepare silver bath and use same for eight weeks with good reticulin fibres staining. This finding can potentially prevent the stress of having to prepare the solution fresh at every point of use and wastage of the remnant solution after use.